Evaluation of the effects of chlorhexidine and several flavonoids as antiviral purposes on SARS-CoV-2 main protease: molecular docking, molecular dynamics simulation studies. Issue 17 (22nd November 2022) - Tatar, Gizem; Salmanli, Merve; Dogru, Yakup; Tuzuner, Tamer
Abstract: The recent outbreak of COVID-19 caused by a new human coronavirus called SARS-CoV-2, is continually causing worldwide human infections and deaths.The main protease (3CLpro), which plays a critical role in the life cycle of the virus, makes it an attractive target for the development of antiviral agents effective against coronaviruses (CoVs).Currently, there is no specific viral protein targeted therapeutics.Therefore, there is a need to investigate an alternative therapy which will prevent the spread of the infection, by focusing on the transmission of the virus.Chlorhexidine (CHX) and flavonoids agents have shown that they have a viral inactivation effect against enveloped viruses, and thus facilitate the struggle against oral transmission.Especially, some flavonoids have very strong antiviral activity in SARS-CoV and MERS-CoV main protease.This study was conducted to evaluate the CHX and flavonoids compounds potential antiviral effects on SARS-CoV-2 main protease through virtual screening for the COVID-19 treatment by molecular docking method.According to the results of this study, CHX, Kaempferol-3-rutinoside, Rutin, Quercetin 3-beta-D-glucoside and Isobavachalcone exhibited the best binding affinity against this enzyme, and also these compounds showed significant inhibitory effects compared to the SARS-CoV-2 main protease crystal structure inhibitor (N3).Especially, these compounds mainly interact with His41, Cys145, His163, Met165, Glu166 and Thr190 in SARS-CoV-2 main protease binding site. Further, MD simulation analysis also confirmed that stability of these interactions between the enzyme and these five compounds.The current study provides to guide clinical trials for broad-spectrum CHX and bioactive flavonoids to reduce the viral load of the infection and possibly disease progression. Communicated by Ramaswamy H. Sarma